2004
DOI: 10.1007/s00467-004-1566-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased cystatin C concentration in urine of nephrotic children

Abstract: The aim of this study was to evaluate changes in urine and plasma concentrations of cystatin C in children with a relapse of the idiopathic nephrotic syndrome(INS). The study group comprised 12 children with INS with proteinuria and 12 children in an 8-week remission,both treated with steroids. Twelve healthy children served as controls. Cystatin C was detectable in the urine of children with proteinuria. The study suggests that massive proteinuria may influence renal cystatin C handling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 11 publications
(9 reference statements)
1
23
1
Order By: Relevance
“…In addition, the absence of circadian variation allows a measurement to be performed rapidly on a random sample (79). Raised urinary CysC concentrations are believed to indicate a tubular abnormality (77,(80)(81)(82).…”
Section: What Is the Renal Fate Of Cysc?mentioning
confidence: 99%
“…In addition, the absence of circadian variation allows a measurement to be performed rapidly on a random sample (79). Raised urinary CysC concentrations are believed to indicate a tubular abnormality (77,(80)(81)(82).…”
Section: What Is the Renal Fate Of Cysc?mentioning
confidence: 99%
“…More recent studies have shown that factors other than renal function, such as C-reactive protein (CRP) and smoking status, may influence serum cystatin C concentrations, so that caution must be used when one is interpreting serum cystatin C levels as a measure of renal function [50]. The findings of cystatin C in the urine during glomerular and tubular injury also casts some doubt on the ability of serum cystatin C to accurately estimate GFR [51,52].…”
Section: Cystatin Cmentioning
confidence: 99%
“…where GFR (A)=Dose/[exp (A)/α], and C1=0.9908 and C2=−0.001218, as generated by Brochner-Mortensen in adults by comparing with plasma disappearance curves for 51 Cr-EDTA. Similar constants have been generated for children by Brochner-Mortensen [55], using comparable methodology (C1=1.01; C2=−0.0017), and recently by us in the CKiD pilot study [30] (C1=0.9950; C2=−0.001159).…”
Section: Single-injection Clearance Techniquesmentioning
confidence: 99%
See 2 more Smart Citations